A study of incidence, causes and management of cut throat injuries - Kumar Chappidi, Aruna; Chilukuri, Anita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Cut throat injuries is trauma that needs prolonged hospitalization, high cost of health care and reduced quality of life and above all death. The aim of the study was to study on cut throat of injuries including its incidence factors provoked and management. Methods: it is prospective study conducted for a period of 2 years. A total of 30 cases of cut throat injuries were included in the study of patients from age group 5-70 yrs. Results: Male to female ratio was (9:1). Cut throat injury was more common in males who came from rural area. Most of them were unemployed and of low socioeconomic group and of low education level. Cut throat injuries were common in Hindu religion followed by Muslims. The most common cause of cut throat injury in our study was homicidal 17(56.6%) followed by suicidal 9 (30%) and accidental 4(13.3%). In our study 11(36.6%) cut throats were superficial and 19 (63.33%) were deep. 19 (63.33) cases sustained grieveous injury with 7 patients were dead. In all the cases (100%) skin, soft tissue and small vessels were severed. The laryngotracheal injury was present in 12 cases. The majority of patients reached the hospital between 6-10 hours. Simple wound closure was done in 17 cases. 30 patients 23 patients had improved in follow up with no complaint of alteration in voice. 12 (40%) patients had stay of around 0–10 days and with only 10 (33.33%). Conclusions: with the advent of newer diagnostic modalities management of cut throat injuries which allow more precise and better management of cut throat injuries. The management of cut throat injuries require a multidisciplinary approach requiring the close collaboration of the otolaryngologist, the anaesthetist and the psychiatrist.